ZMAT3 hypomethylation contributes to early senescence of preadipocytes from healthy first‐degree relatives of type 2 diabetics. Issue 3 (11th February 2022) - Spinelli, Rosa; Florese, Pasqualina; Parrillo, Luca; Zatterale, Federica; Longo, Michele; D'Esposito, Vittoria; Desiderio, Antonella; Nerstedt, Annika; Gustafson, Birgit; Formisano, Pietro; Miele, Claudia; Raciti, Gregory Alexander; et al.
Abstract: Senescence of adipose precursor cells (APC) impairs adipogenesis, contributes to the age‐related subcutaneous adipose tissue (SAT) dysfunction, and increases risk of type 2 diabetes (T2D). First‐degree relatives of T2D individuals (FDR) feature restricted adipogenesis, reflecting the detrimental effects of APC senescence earlier in life and rendering FDR more vulnerable to T2D. Epigenetics may contribute to these abnormalities but the underlying mechanisms remain unclear. In previous methylome comparison in APC from FDR and individuals with no diabetes familiarity (CTRL), ZMAT3 emerged as one of the top‐ranked senescence‐related genes featuring hypomethylation in FDR and associated with T2D risk. Here, we investigated whether and how DNA methylation changes at ZMAT3 promote early APC senescence. APC from FDR individuals revealed increases in multiple senescence markers compared to CTRL. Senescence in these cells was accompanied by ZMAT3  hypomethylation, which caused ZMAT3 upregulation. Demethylation at this gene in CTRL APC led to increased ZMAT3 expression and premature senescence, which were reverted by ZMAT3  siRNA. Furthermore, ZMAT3 overexpression in APC determined senescence and activation of the p53/p21 pathway, as observed in FDR APC. Adipogenesis was also inhibited in ZMAT3 ‐overexpressing APC. In FDR APC, rescue of ZMAT3  methylation through senolytic exposure simultaneously downregulated ZMAT3 expression and improved adipogenesis. Interestingly, in human SAT, aging and T2D were associated with significantly increased expression of both ZMAT3 and the P53  senescence marker. Thus, DNA hypomethylation causes ZMAT3 upregulation in FDR APC accompanied by acquisition of the senescence phenotype and impaired adipogenesis, which may contribute to FDR predisposition for T2D. Abstract : The senescence of adipose precursor cells (APC) contributes to the increased risk of Type 2 Diabetes (T2D) in both elderly subjects and young and non‐obese first‐degree relatives of T2D patients (FDR). DNA hypomethylation in the APC from FDR individuals leads to an upregulation of ZMAT3 which activates the p53/p21 pathway, causing the acquisition of the senescence phenotype and impaired adipogenesis in these progenitor cells.